Antibodies to malaria vaccine candidates are associated with chloroquine or sulphadoxine/pyrimethamine treatment efficacy in children in an endemic area of Burkina Faso - Diarra, Amidou; Nebie, Issa; Tiono, Alfred; Soulama, Issiaka; Ouedraogo, Alphonse; Konate, Amadou; Theisen, Michael; Dodoo, Daniel; Traore, Alfred; Sirima, Sodiomon B. (Malaria Journal, 2012)
Abstract Background Patient immune status is thought to affect the efficacy of anti-malarial chemotherapy. This is a subject of some importance, since evidence of immunity-related interactions may influence our use of chemotherapy in populations with drug resistance, as well as assessment of the value of suboptimal vaccines. The study aim was to investigate relationship between antibodies and anti-malarial drug treatment outcomes. Methods Some 248 children aged 0.5 and 15 years were recruited prior to the high malaria transmission season. Venous blood (5 ml) was obtained from each child to measure antibody levels to selected malaria antigens, using ELISA. Blood smears were also performed to assess drug efficacy and malaria infection prevalence. Children were actively followed up to record clinical malaria cases. Results IgG levels to MSP3 were always higher in the successfully treated group than in the group with treatment failure. The same observation was made for GLURP but the reverse observation was noticed for MSP1-19. Cytophilic and non-cytophilic antibodies were significantly associated with protection against all three antigens, except for IgG4 to MSP1-19 and GLURP. Conclusion Acquired anti-malarial antibodies may play an important role in the efficacy of anti-malarial drugs in younger children more susceptible to the disease.